Training on Utilizing Market Place Opportunities for Students Senior Hight School in Nazhatut Thullab Prajjan Sampang - Sinta Alfiani; Muhoffifah; Zairina (Jurnal Pengabdian Masyarakat (JUDIMAS), 2024)
Current technological developments provide opportunities for the business world to develop very quickly. One of them is the increasing popularity of online businesses by using the internet to carry out transactions and promotions. Online business can be an option for building a business. In the 2013 education curriculum, entrepreneurship is taught to all high school students with the aim of fostering an entrepreneurial spirit from an early age. To support this government program and take advantage of the ease of communication technology and the internet, basic training in online business is carried out using only gadget devices that are very close to our daily lives. The aim of this training is not only to produce young entrepreneurs, but also to encourage students to carry out productive activities by using student gadgets to start online businesses. Training was carried out for students at Prajjan Camplong High School. This training activity uses survey, lecture and mentoring methods to create an account on Shopee. The targets of this activity include students being able to start useful activities by doing online business using their gadget devices. Apart from that, students can become graduates who have business skills that can create new jobs.